A case of acute promyelocytic leukemia variant with derivative chromosome 3 der(3)t(3;8) associated with 8q partial gain - Filomena Nozza (Molecular Cytogenetics, 2019)
Abstract Background Acute promyelocytic leukemia (APL) is characterized by fusion of PML/RARα genes as a result of t(15;17)(q24;q21). APL is now one of the curable hematological malignancies thanks to molecularly targeted therapies based on all-trans retinoic acid (ATRA) and arsenic trioxide (ATX). Extramedullary (EM) relapse is a rare event in APL, ear involvement being even more infrequent, with only six cases so far described. About 30–35% of patients with newly diagnosed APL have additional cytogenetics abnormalities, whose prognostic significance is still controversial. The most common additional aberration is trisomy 8 or partial gain 8q. Case presentation We describe here a novel unbalanced translocation der(3)t(3;8)(q29;q23.3-q24.3) associated with 8q partial gain in a 41 year-old man affected by APL in molecular remission after first line treatment, who had a responsive EM relapse in the auditory canal. Conclusions EM relapse is a rare event in APL and ear involvement is even more infrequent. To our knowledge, this is the first reported case of APL with a new der(3)t(3;8)(q29;q23.3-q24.3) and 8q partial gain associated with t(15;17)(q24;q21). Despite the recurrence of the disease at EM level, the clinical outcome of this patients was favorable.